The Autonomy of the Åland Islands : Constitutional and International Law Challenges - Alfredsson, Gudmundur; Lindholm, Göran (Human Rights and Humanitarian Law E-Books Online, Collection 2024., 2025)
Published on occasion of the 100 year anniversary of the Åland Islands' autonomy, this book brings up and discusses a number of challenging issues, from constitutional and international law perspectives, concerning both the Åland situation and autonomy in general. Among the questions raised are: Is autonomy part of international law and which international organisations may have jurisdiction? Is autonomy a human right or is it about the prevention of violent conflicts? Does the Åland Autonomy constitute a useful model for other minority groups? Do the Åland Islands stand to benefit from anything in international law, be it substantive or procedural?